Interactions between allosteric modulators and 4-DAMP and other antagonists at muscarinic receptors: potential significance of the distance between the N and carboxyl C atoms in the molecules of antagonists - Lysíková, M; Havlas, Z; Tucek, S (Neurochemical research, 2001)
Allosteric enhancement of the affinity of muscarinic receptors for their ligands offers a new way to influence cholinergic neurotransmission. The structure of the allosteric binding domain(s) and the features of agonists, antagonists and modulators which determine the occurrence of either positive or negative cooperativity require clarification. We tested interactions between allosteric modulators alcuronium, strychnine and brucine and eight antagonists at muscarinic receptors expressed in CHO cells. In experiments with unlabeled antagonists, all three modulators enhanced the affinity for 4-diphenylacetoxy-N-dimethylpiperidinium (4-DAMP) at the M2 receptors, and strychnine did so also at the M4 receptors. Positive interactions were also observed between alcuronium and L-hyoscyamine (M2) and scopolamine (M2), between strychnine and butylscopolamine (M4), L-hyoscyamine (M2 and M4) and scopolamine (M4), and between brucine and scopolamine (M2). Positive effects of alcuronium, strychnine and brucine on the affinity of the M2 receptors for 4-DAMP have been confirmed by direct measurements of the binding of [3H]-4-DAMP. A comparison of molecular models of several antagonists which are esters revealed that antagonists in which the distance between the N and the carboxyl C atoms corresponds to five chemical bonds are more likely to display positive cooperativity with alcuronium at the M2 receptors than the antagonists in which the N-carboxyl C distance corresponds to four chemical bonds.
Keywords: CHO buňky; křečci praví; tritium; strychnin; radioligandová zkouška; Alcuronium; zvířata; antagonisté muskarinových receptorů; CHO Cells; Piperidines; alkuronium; Strychnine; Tritium; Radioligand Assay; alosterická regulace; N-Methylscopolamine; Cricetinae; piperidiny; Animals; N-methylskopolamin; Muscarinic Antagonists; Allosteric Regulation